Measuring personal exposure to fine particulate matter (PM2.5) among rural Honduran women: A field evaluation of the Ultrasonic Personal Aerosol Sampler (UPAS). (February 2019) - Pillarisetti, Ajay; Carter, Ellison; Rajkumar, Sarah; Young, Bonnie N.; Benka-Coker, Megan L.; Peel, Jennifer L.; Johnson, Michael; Clark, Maggie L.
Abstract: We measured 24-hour average personal exposure to fine particulate matter (PM2.5 ) among rural Honduran women using a lightweight, gravimetric monitor – the Ultrasonic Personal Aerosol Sampler (UPAS). Performance of the UPAS was compared with a commonly used gravimetric pump, cyclone, and filter sampling system. We observed strong agreement and correlation (Spearman ρ = 0.91; PM2.5 concentration range: 19–120 μg/m 3 ) between 43 paired measures, supporting the use of the UPAS as a personal exposure monitor for household air pollution studies. Highlights: Common methods for measuring personal exposure to PM mass have involved devices that are cumbersome to wear We compared the performance of Ultrasonic Personal Aerosol Samplers to standard methods for 24-h PM2.5 among biomass users Given strong observed, the UPAS may be viable for personal PM2.5 assessments, particularly for cookstove-related studies